PENGARUH PERILAKU KEPEMIMPINAN, PENGAWASAN INTERNAL, DAN MOTIVASI TERHADAP KINERJA PEGAWAI PADA BADAN KEUANGAN DAN ASET DAERAH KABUPATEN KONAWE SELATAN - Masriani Masriani; Nurwati Nurwati; Salma Saleh (Pascasarjana Universitas Halu Oleo, 2021)
The purpose of this study was to determine the effect of: 1) leadership behavior on employee performance. 2) internal control over employee performance. 3) motivation towards employee performance. 4) leadership behavior, internal control and motivation on employee performance. The research method is to use quantitative research. The data used are secondary and primary data. Data analysis using SPSS software version 20. The sampling technique uses saturated sample amounted to 51 employees at the Regional Financial and Asset Agency of South Konawe Regency. The results showed that; 1) leadership behavior has a positive and significant effect on employee performance. 2) internal controlpositive and significant effect on employee performance. 3) motivationpositive and significant effect on employee performance. 4) leadership behavior, internal control and motivationpositive and significant effect on employee performance.